A method for regenerating a deactivated copper-bismuth catalyst
By using nitrous oxide in the regeneration process of copper bismuth catalyst for low-temperature thermal oxidation treatment and combined with anhydride modified polypropylene carbonate for defective position modification, the problem of copper oxide particles agglomeration is solved and the catalytic activity is significantly improved and the effect of removing surface deposits.
Patent Information
- Application Number
- CN202411419510.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The prior art In the regeneration process of copper bismuth catalyst, the agglomeration of copper oxide particles is easily caused, resulting in a decrease in catalytic activity.
Nitrous oxide is used for low-temperature thermal oxidation treatment, and defective modification is carried out in combination with anhydride modified polypropylene carbonate to avoid agglomeration of copper oxide particles.
The catalytic activity of the catalyst after regeneration was significantly improved, the catalytic activity recovery rate reached more than 90%, and the content of surface sediments was controlled within 2.1%.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst regeneration, and in particular to a regeneration method for a deactivated copper-bismuth catalyst. Background Art
[0002] Currently, biodegradable plastics produced from BDO (1,4-butanediol), such as polybutylene terephthalate-adipate, polybutylene succinate and polybutylene terephthalate, are widely used in related fields and are in great demand.
[0003] The acetylene aldehyde method produces BYD (1,4-butynediol), which can then be catalytically hydrogenated to produce BDO, which is the main production process of BDO. The acetylene aldehyde method uses a copper-bismuth catalyst as a catalyst for the acetylene aldehyde reaction. The structural properties and surface conditions of the copper-bismuth catalyst have a great influence on the catalytic effect.
[0004] However, during the use of copper-bismuth catalysts, excessive surface deposits cover the active sites of the catalyst, causing the catalyst activity to decrease. This is mainly manifested in a decrease in the production of butanediol, which does not meet production requirements and requires regular replacement, discharge, replacement or regeneration.
[0005] CN113209980A discloses a method for regenerating a deactivated copper-bismuth catalyst, which uses a spray of copper-bismuth waste catalyst aqueous solution droplets mixed with high-temperature flue gas to regenerate the waste catalyst, and the high-temperature flue gas is generated by aerobic combustion of a mixture of one or more of natural gas, diesel, methanol and hydrogen. This scheme uses high-temperature gas to fully mix with the waste catalyst droplets, so that the impurities in the waste catalyst are removed to the maximum extent at a suitable temperature, thereby achieving the regeneration of the waste catalyst. However, this method removes the organic phase on the copper-bismuth catalyst by aerobic combustion, so that the temperature of the atomized droplets of the waste catalyst powder aqueous solution mixed with the high-temperature flue gas reaches 600-800°C, the treatment conditions are too harsh, and the activity of the regenerated catalyst decreases.
[0006] CN115945228A discloses a method for regenerating a deactivated copper-bismuth catalyst, which mainly separates the deactivated copper-bismuth catalyst into solid and liquid by centrifugation, dries the separated product, and then calcines it at high temperature to obtain a regenerated catalyst. This method cannot completely separate the sediment on the surface of the deactivated copper-bismuth catalyst, and the catalytic activity of the regenerated catalyst is average.
[0007] It can be seen from this that the existing technology for regenerating copper-bismuth catalysts mainly revolves around the treatment of surface deposits, but the existing technology currently has a poor regeneration effect on the copper-bismuth catalyst. Summary of the invention
[0008] During the use of the catalyst, the copper oxide active sites of the catalyst are reduced to cuprous oxide by formaldehyde, and then react with acetylene to form copper acetylene, which catalyzes the acetylene-aldehyde reaction. During the reaction, the accumulated organic deposits (polyacetylene, 1,4-butenediol, propargyl alcohol and polyformaldehyde, etc.) and carbon deposits cover the catalyst surface and block the catalyst pores, causing the catalyst to deactivate.
[0009] The prior art usually uses a high-temperature calcination method to oxidatively decompose organic deposits and carbon deposits on the catalyst. During the high-temperature calcination process, acetylene copper is simultaneously oxidized to copper oxide. The inventors have conducted multiple studies and found that ① the reaction of acetylene ketone to copper oxide is too intense; ② the high-temperature treatment environment will cause the active sites to agglomerate, resulting in a decrease in the activity of the regenerated catalyst.
[0010] Therefore, the existing conventional air oxidation, high-temperature flue gas oxidation and other strong oxidative regeneration methods are prone to cause active site agglomeration, and the particle size of the regenerated CuO is much larger than that of the fresh catalyst, resulting in a decrease in the activity of the regenerated catalyst. In addition, the Tammann temperature of copper oxide is relatively low at 527°C. When in a high temperature environment, the atoms in the CuO lattice begin to loosen, and the chemical reaction properties are enhanced, resulting in an increase in CuO grains. Therefore, the particle size of CuO in the catalyst after high-temperature regeneration increases significantly.
[0011] The prior art usually uses air or high-temperature flue gas with relatively strong oxidizing properties to oxidize copper acetylene. For example, CN113209980A uses high-temperature flue gas to oxidatively regenerate the catalyst; while CN115945228A calcines it in air for oxidative regeneration. Both use strong oxidizing gases and adopt a high-temperature oxidizing environment, resulting in serious agglomeration. It is these agglomerated particles that cause the catalytic activity of the catalyst to drop significantly after regeneration.
[0012] In order to solve the above technical problems, the present invention provides a regeneration method for a deactivated copper-bismuth catalyst. By using nitrous oxide to oxidatively regenerate the deactivated copper-bismuth catalyst, the agglomeration of copper oxide can be avoided, thereby significantly improving the catalytic activity of the regenerated catalyst, and the application prospect is broad.
[0013] To achieve this object, the present invention adopts the following technical solutions:
[0014] In a first aspect, the present invention provides a method for regenerating a deactivated copper-bismuth catalyst, the regeneration method comprising:
[0015] The deactivated copper-bismuth catalyst is subjected to low-temperature thermal oxidation treatment in a nitrous oxide atmosphere to obtain a catalyst after low-temperature thermal oxidation treatment.
[0016] The present invention uses nitrous oxide with relatively low oxidizing power at low temperature (≤500°C) as the regeneration gas, which can achieve the effect of slowly oxidizing the regenerated catalyst and slow down the agglomeration of CuO particles at the active site. The CuO particle size of the active site of the catalyst after regeneration by nitrous oxide is almost close to the CuO particle size level of the unused fresh catalyst, and the activity of the regenerated catalyst is more than 90% of the activity of the fresh catalyst.
[0017] Preferably, the temperature of the low-temperature thermal oxidation treatment is 350~500℃, for example, it can be 350℃, 367℃, 384℃, 400℃, 417℃, 434℃, 450℃, 467℃, 484℃ or 500℃, etc.; the duration of the low-temperature thermal oxidation treatment is 10~30h, for example, it can be 10h, 13h, 15h, 17h, 19h, 22h, 24h, 26h, 28h or 30h, etc.
[0018] In the present invention, the temperature of the nitrous oxide atmosphere combined with the low-temperature hot oxygen treatment is controlled within the range of 350-500° C., which can effectively prevent the growth of copper oxide particles in the regenerated catalyst and ensure the catalytic activity of the regenerated catalyst.
[0019] It is worth noting that the deactivated copper-bismuth catalyst of the present invention is a catalyst used in the acetylene-aldehyde reaction. During the use of the catalyst, the active copper oxide sites of the catalyst are reduced to cuprous oxide by formaldehyde, and then react with acetylene to form acetylene copper, which plays a catalytic role in the acetylene-aldehyde reaction. During the reaction, the accumulated surface deposits cover the catalyst surface and block the catalyst pores, resulting in the deactivation of the catalyst; the surface deposits include organic deposits and carbon deposits, and the organic deposits include any one or a combination of at least two of polyacetylene, 1,4-butenediol, propargyl alcohol or polyformaldehyde.
[0020] It is worth noting that the active component of the deactivated copper-bismuth catalyst of the present invention is CuO. It is well known that the carrier of the fresh copper-bismuth catalyst is magnesium silicate and the auxiliary agent is bismuth oxide, which is used to inhibit the formation of polyacetylene during the reaction.
[0021] Preferably, the step of low-temperature thermal oxidation treatment comprises: heating the deactivated copper-bismuth catalyst to a low-temperature thermal oxidation treatment temperature under a nitrogen atmosphere, and then gradually introducing nitrous oxide for oxidation.
[0022] Preferably, during the process of gradually introducing nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y;
[0023] The initial space velocity x of nitrous oxide is recorded as x0, where x0 is at most 50h -1 , preferably at least 25h -1 , where the value range of x0 can be, for example, 25h-1 、30h -1 、32h -1 , 35h -1 , 40h -1 , 42h -1 , 45h -1 、48h -1 or 50h -1 wait.
[0024] x value is 15~90h -1 ·h -1 The speed of the airspeed value is increased by 15h, and the y value is reduced accordingly; the growth rate of the x value can be, for example, 15h -1 ·h -1 , 20h -1 ·h -1 , 25h -1 ·h -1 、30h -1 ·h -1 , 40h -1 ·h -1 , 45h -1 ·h -1 , 50h -1 ·h -1 , 55h -1 ·h -1 、60h -1 ·h -1 、70h -1 ·h -1 , 80h -1 ·h -1 or 90h -1 ·h -1 wait.
[0025] Optionally, the space velocity x+y of the total gas volume in the low-temperature thermal oxidation treatment remains constant, and the space velocity x+y is controlled at 500-1000 h -1 , for example, it can be 500h -1 、550h -1 、600h -1 、650h -1 、700h -1 、750h -1 、800h -1 , 820h -1 , 900h -1 、950h -1 or 1000h -1 wait.
[0026] In the present invention, x0 will affect the catalyst regeneration activity. If x0 is too small, the nitrous oxide consumption will be too large, and the regeneration cost will increase. If x0 is too large, the copper oxide particle size will be too large, which will lead to insufficient catalyst regeneration activity.
[0027] The increasing speed of x will affect the regeneration activity of the catalyst. If the increasing speed of x is too slow, the regeneration cost will increase. If the increasing speed of x is too fast, the copper oxide particles will be too large, which will lead to insufficient catalyst regeneration activity.
[0028] The oxidation rate of nitrous oxide gas to copper acetylene, organic matter accumulated on the catalyst surface and polypropylene carbonate is relatively low, and the space velocity of the total gas volume needs to be 500~1000h -1 , 10~30h to achieve full oxidation. The space velocity of the total gas volume is less than 500h -1 The reaction heat generated by the oxidation of the system cannot be taken away, resulting in local overheating and agglomeration of copper oxide; more than 1000h -1 When the surface deposits are calcined and oxidized at 350-500°C, the active site particles move actively, which easily leads to agglomeration.
[0029] Preferably, the regeneration method further comprises: before the thermal oxidation treatment, the deactivated copper-bismuth catalyst is first subjected to defect site modification treatment.
[0030] The defect site modification treatment comprises: mixing a deactivated copper-bismuth catalyst and a modifier, and sequentially performing stirring and solid-liquid separation to obtain a modified deactivated copper-bismuth catalyst.
[0031] Preferably, the modifier is a solution of anhydride-modified polypropylene carbonate.
[0032] In the present invention, when nitrous oxide is used for low-temperature calcination, a modifier is used to treat the catalyst in advance. The modifier contains anhydride-modified polypropylene carbonate, and its anhydride group can form a stable ester bond with the abundant hydroxyl groups on the carrier (magnesium silicate) of the copper bismuth catalyst. During the subsequent heating and oxidation treatment process, a defect site can be formed at the junction of the modifier and the carrier. The defect can hinder the agglomeration of CuO. The distribution of CuO at the site is stable, which can greatly inhibit the movement of CuO particles in the subsequent oxidation process and generate agglomeration.
[0033] Preferably, the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:(1-10), for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, etc.;
[0034] The present invention further preferably controls the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst within the above range. When too little anhydride-modified polypropylene carbonate is added, there is no obvious improvement effect on the agglomeration problem caused by further inhibiting the movement of CuO particles; when too much anhydride-modified polypropylene carbonate is added, it will lead to the loss of CuO in the active site of the catalyst.
[0035] And / or, the anhydride content of the anhydride-modified polypropylene carbonate is 1-3%, for example, 1%, 1.2%, 1.4%, 1.5%, 1.7%, 1.9%, 2%, 2.2%, 2.4% or 3%, etc.;
[0036] The present invention further preferably controls the content of acid anhydride in the acid anhydride-modified polypropylene carbonate within the above range. When the acid anhydride content is too low, there is no obvious improvement effect on the agglomeration problem caused by inhibiting the movement of CuO particles; when the acid anhydride content is too high, it leads to the loss of CuO at the active site of the catalyst. Sufficient acid anhydride-modified polypropylene carbonate can fully react with the hydroxyl group on the deactivated catalyst, can fully decompose after oxidation and form sufficient "defective" sites, increase the stability of the copper oxide particles, and obtain smaller CuO particles at the active site of the catalyst.
[0037] And / or, there is no specific restriction on the content of the solute in the solution of the anhydride-modified polypropylene carbonate, as long as the solute can be completely dissolved in the solvent and can well wet the catalyst, for example, it can be 10wt%, 9.5wt%, 9wt%, 8.5wt%, 8wt%, 7.5wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt% or 2wt%, etc.
[0038] And / or, the solvent in the solution of the anhydride-modified polypropylene carbonate includes dichloromethane and / or tetrahydrofuran.
[0039] Preferably, the stirring condition satisfies at least one of the following:
[0040] The stirring temperature is 150-200°C, for example, 150°C, 162°C, 173°C, 184°C, 195°C or 200°C;
[0041] The stirring speed is 150-800 r / min, for example, 150 r / min, 220 r / min, 295 r / min, 365 r / min, 430 r / min, 510 r / min, 585 r / min, 650 r / min, 720 r / min or 800 r / min, etc.;
[0042] The stirring time is 4 to 24 hours, for example, it can be 4 hours, 7 hours, 9 hours, 11 hours, 13 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0043] The present invention preferably controls the reaction efficiency of the anhydride-modified polypropylene carbonate and the deactivated catalyst by controlling the stirring temperature, speed and time, which helps to control the "defective" sites of the catalyst and control the grain growth of copper oxide at the active sites of the catalyst during the oxidation process. The stirring temperature is allowed to fluctuate within the range of 150 to 200° C., and can also be kept constant at the initial solution temperature or at any temperature within the range of 150 to 200° C., mainly to control the anhydride-modified polypropylene carbonate to be fully dissolved in the solvent.
[0044] Preferably, the regeneration method further comprises, after the thermal oxidation treatment, calcining the catalyst after the thermal oxidation treatment when the sediment loading in the catalyst after the thermal oxidation treatment is higher than 3 wt %.
[0045] Since the process of thermal oxidation treatment using nitrous oxide needs to consider the effect of the reaction conditions of acetylene ketone converted into copper oxide during the regeneration process on the particle size of CuO, the space velocity of nitrous oxide, the temperature and time of thermal oxidation treatment are all subject to certain constraints. Therefore, compared with the prior art, its ability to treat surface deposits of waste copper bismuth catalyst under the aforementioned restricted oxidation conditions is limited. In this case, roasting treatment needs to be added. At this time, since acetylene copper has been completely converted into CuO during the roasting treatment, the agglomeration problem caused by the acetylene copper reaction has been solved. In the subsequent roasting treatment process, whether it is oxygen atmosphere, high-temperature flue gas or nitrous oxide, it will no longer cause significant changes in the CuO particle size.
[0046] Preferably, the calcination temperature is within 500°C, for example, it may be 500°C, 490°C, 480°C, 470°C, 460°C, 450°C, 400°C, 380°C or 350°C.
[0047] And / or, the atmosphere of the roasting treatment is an oxidizing atmosphere; the oxidizing atmosphere includes any one of air, high-temperature flue gas or nitrous oxide, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of air and high-temperature flue gas, a combination of nitrous oxide and high-temperature flue gas, and a combination of air and nitrous oxide.
[0048] Compared with the prior art, the present invention has at least the following beneficial effects:
[0049] (1) The regeneration method of the deactivated copper-bismuth catalyst provided by the present invention can effectively avoid the agglomeration of copper oxide during the regeneration process, and better improve the catalytic activity of the catalyst after regeneration. The decrease value of the catalytic activity of the catalyst after regeneration is within 12%, preferably within 6%, and the catalytic activity recovery rate after regeneration is above 80%, preferably above 90%;
[0050] (2) The regeneration method of the deactivated copper-bismuth catalyst provided by the present invention uses nitrous oxide for oxidation and anhydride-modified polypropylene carbonate for defect site modification. The two can synergistically ensure that the grain size of copper oxide does not grow during the regeneration process. The particle size of CuO particles in the catalyst after regeneration is within 22.1 nm, preferably within 19.1 nm;
[0051] (3) The regeneration method of the deactivated copper-bismuth catalyst provided by the present invention preferably performs a calcination treatment at the end, which can be combined with a thermal oxidation treatment step to further remove surface deposits on the deactivated copper-bismuth catalyst. Under preferred conditions, the content of surface deposits in the regenerated catalyst is within 3%, preferably within 2.10%, thereby achieving efficient regeneration of the deactivated copper-bismuth catalyst. DETAILED DESCRIPTION
[0052] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0053] Terms and Definitions
[0054] Deactivated waste copper-bismuth catalyst: The active site Cu content of fresh copper-bismuth catalyst is usually 38-42%. The formaldehyde conversion rate of fresh copper-bismuth catalyst after activation and stabilization is ≥50%. During long-term use, as the deposits on the catalyst surface increase, when the formaldehyde conversion rate of the copper-bismuth catalyst is lower than 30%, the copper-bismuth catalyst in the system is called deactivated waste copper-bismuth catalyst. The formaldehyde conversion rate of fresh copper-bismuth catalyst after activation and stabilization refers to the formaldehyde conversion rate of the catalyst measured after the conductivity of the solution of fresh copper-bismuth catalyst drops to 500μs / cm after cyclic use, which is the formaldehyde conversion rate of the fresh copper-bismuth catalyst after activation and stabilization.
[0055] The copper content of catalyst A is 40.9%, the initial catalytic activity is 61.1%, the catalytic activity of catalyst A when deactivated is 25%, the surface sediment loading of catalyst A when deactivated is 75%, and the particle size of CuO particles when catalyst A is deactivated is 18.1 nm;
[0056] The copper content of catalyst B is 39.5%, the initial catalytic activity is 57.3%, the catalytic activity of catalyst B when deactivated is 29%, the surface sediment loading of catalyst B when deactivated is 65%, and the particle size of CuO particles when catalyst B is deactivated is 18.5 nm;
[0057] The copper content of catalyst C is 41%, the initial catalytic activity is 63.5%, the catalytic activity of catalyst C when deactivated is 22%, the surface sediment loading of catalyst C when deactivated is 82%, and the particle size of CuO particles of catalyst C when deactivated is 16.8 nm;
[0058] The copper content of catalyst D is 39%, the initial catalytic activity is 56%, the catalytic activity of catalyst D when deactivated is 28.7%, the surface sediment loading of catalyst D when deactivated is 62%, and the particle size of CuO particles of catalyst D when deactivated is 17.7 nm.
[0059] Reaction space velocity: the amount of gas treated by a unit volume of catalyst per unit time, in m 3 / (m 3 catalyst·h), which can be simplified to h -1 In actual operation, the control error of reaction air velocity is within ±1 h -1 is allowed.
[0060] The anhydride-modified polypropylene carbonate refers to maleic anhydride-grafted polypropylene carbonate. Such materials are usually prepared by reactive twin-screw extrusion granulation. The anhydride-modified polypropylene carbonate used in the embodiments of the present invention is homemade, and the preparation method is as follows:
[0061] PPC (polypropylene carbonate), MAH (maleic anhydride) and DCP (dicumyl peroxide) were mixed evenly in a certain proportion, and then added into a twin-screw extruder for extrusion granulation to obtain anhydride-modified polypropylene carbonate; the extruder was from Nanjing Keya Extrusion Equipment Co., Ltd., model HK-26, with an aspect ratio of 48:1;
[0062] The extruder temperature was set at 180 °C and the speed was 190 r / min;
[0063] Anhydride-modified polypropylene carbonate A: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) according to the mass ratio of 100:2:0.2, the grafting rate was measured to be 1%;
[0064] Anhydride-modified polypropylene carbonate B: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) in a mass ratio of 100:4:0.3, the grafting rate was measured to be 2.5%;
[0065] Anhydride-modified polypropylene carbonate C: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) according to the mass ratio of 100:5:0.35, the grafting rate was measured to be 3%;
[0066] The content of anhydride is the maleic anhydride grafting rate, which is usually tested by titration. The method for determining the maleic anhydride grafting rate disclosed in the article “Calderón BA, Soule J, Sobkowicz M J. Synthesis and characterization of compatibilizers for blends of polypropylene carbonate and polybutylene succinate via free-radical grafting of maleic anhydride[J]. Journal of Applied Polymer Science, 2019, 136(21): 47553” can be referred to.
[0067] Test method:
[0068] CuO particle size: The CuO particle size was measured by conventional XRD. The sample powder was tested using a Bruker D8QUEST X-ray diffractometer from Bruker, Germany. The test wavelength was λ = 1.54059Å. The sample was tested for 1 hour at a conventional working voltage (40kV) and working current (40mA). The test angle range was 10~80°, and the diffraction pattern of the catalyst was measured. The particle size of copper oxide in the active site of the catalyst is calculated. k is a constant with a value of 0.89, λ is the wavelength of the X-ray with a value of 0.154059 nm, β is the half-maximum width (FWHM) of the diffraction peak, and θ is the diffraction angle.
[0069] Conversion degree of acetylene ketone: Hydrogen spectrum detection is used to characterize the degree of conversion of acetylene ketone to CuO in the waste copper-bismuth catalyst sample. The 1HMASNMR experiments of the samples are all carried out on a solid-state nuclear magnetic resonance spectrometer of model Bruker400WBAVANCEⅢ produced by Bruker Instruments of Germany, with a magnetic field strength of 9.4T. The instrument is equipped with a 4mm triple-resonance broadband solid probe. The resonance frequency of 1H is 400.13MHz. All experiments are carried out at room temperature and the rotation speed is 12kHz. 1HMASNMR uses single pulse acquisition and the number of scans is 100 times. The pulse width of 1HMASNMR is 0.026s, and the scanning spectrum width is 100ppm. The reduction in the H peak area of acetylene before and after the regeneration of the deactivated copper-bismuth catalyst is the degree of conversion of acetylene copper.
[0070] Surface sediment loading: The surface sediment loading is obtained by calcining at 900°C for 5h, and the mass difference before and after calcination is the loading of the surface sediment.
[0071] Evaluation of catalyst activity: First, add 35 ml of 36 wt% formaldehyde solution into a three-necked flask, adjust the solution pH to 5 with sodium acetate, and then add 4 g of catalyst sample; then, before the reaction starts, purge the reaction system with nitrogen for 20 min, heat the oil bath temperature to 80 ° C, and then send acetylene gas into the reactor at normal pressure, the flow rate of acetylene is adjusted to 20 ml / min, and the catalyst is pretreated for 2 h; thirdly, after the catalyst pretreatment, the temperature is raised to 90 ° C, and after reacting for 8 h, purge with nitrogen for 30 min to remove the remaining acetylene gas; finally, after cooling to room temperature, filter the reaction liquid to obtain the reaction product, and measure the formaldehyde peak areas X1 and X2 before and after the reaction by gas chromatograph to calculate the formaldehyde conversion rate Y in the reactor, Y=1-X2 / X1. The conversion rate of the fresh copper-bismuth catalyst is not very stable at the beginning of the reaction. After the conductivity of the solution of the fresh copper-bismuth catalyst is circulated and applied, it drops to 500μs / cm for the first time. At this time, the formaldehyde conversion rate of the catalyst measured becomes stable, that is, the formaldehyde conversion rate of the fresh copper-bismuth catalyst after activation and stabilization is the initial catalyst activity value of the catalyst.
[0072] Catalytic activity recovery rate: The initial catalytic activity of the fresh catalyst and the initial catalytic activity of the catalyst after regeneration are measured respectively, and the formaldehyde conversion rate is used to characterize the initial catalytic activity of the catalyst. Catalytic activity recovery rate = initial catalytic activity measured by the regenerated catalyst / initial catalytic activity measured by the fresh catalyst.
[0073] The following examples and comparative examples provide a method for regenerating a deactivated copper-bismuth catalyst, the regeneration method comprising the following steps:
[0074] (1) mixing a deactivated copper-bismuth catalyst and a modifier, stirring at 150-200° C. and 150-800 r / min for 4-24 h, and filtering to obtain a modified deactivated copper-bismuth catalyst;
[0075] The modifier is a solution of anhydride-modified polypropylene carbonate, the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:(1-10); the content of anhydride in the anhydride-modified polypropylene carbonate is 1-3%; the content of solute in the solution of the anhydride-modified polypropylene carbonate is ≤10wt%; the solvent in the solution of the anhydride-modified polypropylene carbonate includes dichloromethane and / or tetrahydrofuran;
[0076] (2) In a nitrogen atmosphere, the modified deactivated copper-bismuth catalyst is heated to a low-temperature thermal oxidation temperature of 350 to 500° C., and then nitrous oxide is gradually introduced to replace nitrogen for oxidation, and the thermal oxidation treatment lasts for 10 to 30 hours;
[0077] During the stepwise introduction of nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y; the initial space velocity x value of nitrous oxide is recorded as x0, wherein x0 is 25-50h -1 ; x value is 15~90h -1 ·h -1 The speed increases the airspeed value and decreases the y value accordingly;
[0078] The space velocity x+y of the total gas volume in the low-temperature thermal oxidation treatment remains constant, and the space velocity x+y is controlled at 500-1000 h -1 ;
[0079] (3) When the deposit loading in the catalyst after thermal oxidation treatment is higher than 3 wt %, the catalyst after thermal oxidation treatment is calcined within 500° C. in an oxidizing atmosphere to obtain a regenerated copper-bismuth catalyst.
[0080] Example 1
[0081] A method for regenerating a deactivated copper-bismuth catalyst, wherein the deactivated copper-bismuth catalyst comes from a deactivated copper-bismuth catalyst A, and the deactivated copper-bismuth catalyst A is regenerated, comprising the following steps:
[0082] (1) mixing a deactivated copper-bismuth catalyst and a modifier, stirring at 200° C. and 300 r / min for 15 h, and filtering to obtain a modified deactivated copper-bismuth catalyst;
[0083] The modifier is a solution of anhydride-modified polypropylene carbonate, the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:1; the anhydride-modified polypropylene carbonate is anhydride-modified polypropylene carbonate A; the content of the solute in the anhydride-modified polypropylene carbonate solution is 6wt%; the solvent in the anhydride-modified polypropylene carbonate solution is dichloromethane;
[0084] (2) In a nitrogen atmosphere, the modified deactivated copper-bismuth catalyst is heated to a low-temperature thermal oxidation temperature of 400° C., and then nitrous oxide is gradually introduced to replace nitrogen for oxidation, and the thermal oxidation treatment lasts for 25 hours;
[0085] During the stepwise introduction of nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y; the initial space velocity x value of nitrous oxide is recorded as x0, where x0 is 25h -1 ; x value is 50h -1 ·h-1 The speed increases the airspeed value and decreases the y value accordingly;
[0086] The space velocity x+y of the total gas volume in the low-temperature thermal oxidation treatment is always maintained at 600 h -1 ;
[0087] Determining the conversion degree of copper acetylene in the catalyst after low-temperature thermal oxidation treatment, wherein the conversion degree of copper acetylene is 100%;
[0088] (3) The sediment loading in the catalyst after low-temperature thermal oxidation treatment was determined to be higher than 3 wt %. The catalyst after thermal oxidation treatment was calcined at 500 °C in an air atmosphere for 4 h to obtain a regenerated copper-bismuth catalyst.
[0089] Example 2
[0090] A method for regenerating a deactivated copper-bismuth catalyst, wherein the deactivated copper-bismuth catalyst comes from a deactivated copper-bismuth catalyst B, and the deactivated copper-bismuth catalyst B is regenerated, comprising the following steps:
[0091] (1) mixing a deactivated copper-bismuth catalyst and a modifier, stirring at 150° C. and 800 r / min for 4 h, and filtering to obtain a modified deactivated copper-bismuth catalyst;
[0092] The modifier is a solution of anhydride-modified polypropylene carbonate, the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:5; the anhydride-modified polypropylene carbonate is anhydride-modified polypropylene carbonate B; the content of the solute in the anhydride-modified polypropylene carbonate solution is 10wt%; the solvent in the anhydride-modified polypropylene carbonate solution is dichloromethane;
[0093] (2) In a nitrogen atmosphere, the modified deactivated copper-bismuth catalyst is heated to a low-temperature thermal oxidation temperature of 500° C., and then nitrous oxide is gradually introduced to replace nitrogen for oxidation, and the thermal oxidation treatment lasts for 10 hours;
[0094] During the stepwise introduction of nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y; the initial space velocity x value of nitrous oxide is recorded as x0, where x0 is 50h -1 ; x value is 15h -1 ·h -1 The speed increases the airspeed value and decreases the y value accordingly;
[0095] The space velocity x+y of the total gas volume in the low-temperature thermal oxidation treatment is always maintained at 500 h -1 ;
[0096] Determining the conversion degree of copper acetylene in the catalyst after low-temperature thermal oxidation treatment, wherein the conversion degree of copper acetylene is 100%;
[0097] (3) The sediment loading in the catalyst after low-temperature thermal oxidation treatment was determined to be higher than 3 wt %. The catalyst after thermal oxidation treatment was calcined at 450 °C for 6 h in a high-temperature flue gas atmosphere to obtain a regenerated copper-bismuth catalyst.
[0098] Example 3
[0099] A method for regenerating a deactivated copper-bismuth catalyst, wherein the deactivated copper-bismuth catalyst comes from a deactivated copper-bismuth catalyst C, and the deactivated copper-bismuth catalyst C is regenerated, comprising the following steps:
[0100] (1) mixing a deactivated copper-bismuth catalyst and a modifier, stirring at 175° C. and 150 r / min for 24 h, and filtering to obtain a modified deactivated copper-bismuth catalyst;
[0101] The modifier is a solution of anhydride-modified polypropylene carbonate, the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:10; the anhydride-modified polypropylene carbonate is anhydride-modified polypropylene carbonate A; the content of the solute in the anhydride-modified polypropylene carbonate solution is 8wt%; the solvent in the anhydride-modified polypropylene carbonate solution is dichloromethane / tetrahydrofuran compounded in a mass ratio of 1:1;
[0102] (2) In a nitrogen atmosphere, the modified deactivated copper-bismuth catalyst is heated to a low-temperature thermal oxidation temperature of 450° C., and then nitrous oxide is gradually introduced to replace nitrogen for oxidation, and the thermal oxidation treatment lasts for 20 hours;
[0103] During the stepwise introduction of nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y; the initial space velocity x value of nitrous oxide is recorded as x0, where x0 is 25h -1 ; x value is 90h -1 ·h -1 The speed increases the airspeed value and decreases the y value accordingly;
[0104] The space velocity x+y of the total gas volume in the low-temperature thermal oxidation treatment is always maintained at 1000 h -1 ;
[0105] Determining the conversion degree of copper acetylene in the catalyst after low-temperature thermal oxidation treatment, wherein the conversion degree of copper acetylene is 100%;
[0106] (3) The sediment loading in the catalyst after low-temperature thermal oxidation treatment was determined to be higher than 3 wt %. The catalyst after thermal oxidation treatment was calcined at 475 ° C in a nitrous oxide atmosphere for 8 h to obtain a regenerated copper-bismuth catalyst.
[0107] Example 4
[0108] A method for regenerating a deactivated copper-bismuth catalyst, wherein the deactivated copper-bismuth catalyst comes from a deactivated copper-bismuth catalyst D, and the deactivated copper-bismuth catalyst D is regenerated, comprising the following steps:
[0109] (1) mixing a deactivated copper-bismuth catalyst and a modifier, stirring at 180° C. and 600 r / min for 12 h, and filtering to obtain a modified deactivated copper-bismuth catalyst;
[0110] The modifier is a solution of anhydride-modified polypropylene carbonate, the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:8; the anhydride-modified polypropylene carbonate is anhydride-modified polypropylene carbonate C; the content of the solute in the anhydride-modified polypropylene carbonate solution is 5wt%; the solvent in the anhydride-modified polypropylene carbonate solution is a compound of dichloromethane / tetrahydrofuran in a mass ratio of 7:3;
[0111] (2) In a nitrogen atmosphere, the modified deactivated copper-bismuth catalyst is heated to a low-temperature thermal oxidation temperature of 350° C., and then nitrous oxide is gradually introduced to replace nitrogen for oxidation, and the thermal oxidation treatment lasts for 30 hours;
[0112] During the stepwise introduction of nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y; the initial space velocity x value of nitrous oxide is recorded as x0, where x0 is 45h -1 ; x value is 60h -1 ·h -1 The speed increases the airspeed value and decreases the y value accordingly;
[0113] The space velocity x+y of the total gas volume in the low temperature thermal oxidation treatment is always maintained at 725h -1 ;
[0114] Determining the conversion degree of copper acetylene in the catalyst after low-temperature thermal oxidation treatment, wherein the conversion degree of copper acetylene is 100%;
[0115] (3) The sediment loading in the catalyst after low-temperature thermal oxidation treatment was determined to be 1.9 wt %. The catalyst was not further calcined to obtain a regenerated copper-bismuth catalyst.
[0116] Example 5
[0117] A method for regenerating a deactivated copper-bismuth catalyst. The regeneration method is basically the same as that in Example 1, except that the preparation method does not include step (1), but directly treats the deactivated copper-bismuth catalyst according to steps (2) and (3) to obtain a regenerated copper-bismuth catalyst.
[0118] Example 6
[0119] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method being substantially the same as that of Example 1, the only difference being that in step (1), the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:12, to obtain a regenerated copper-bismuth catalyst.
[0120] Comparative Example 1
[0121] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method being substantially the same as that of Example 5, the only difference being that the thermal oxidation treatment atmosphere in step (2) is replaced by air from nitrous oxide gas to obtain a regenerated copper-bismuth catalyst.
[0122] Comparative Example 2
[0123] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method is basically the same as that in Example 5, the only difference being that the space velocity x+y of the total gas volume in step (2) is controlled at 400 h -1 , and obtain the regenerated copper-bismuth catalyst.
[0124] Comparative Example 3
[0125] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method being substantially the same as that of Example 5, the only difference being that the temperature of the low-temperature thermal oxidation treatment in step (2) is controlled at 300° C., resulting in a conversion degree of copper acetylene in the catalyst after the low-temperature thermal oxidation treatment of only 73%; a regenerated copper-bismuth catalyst is obtained.
[0126] Comparative Example 4
[0127] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method being substantially the same as that of Example 5, the only difference being that the temperature of the low-temperature thermal oxidation treatment in step (2) is controlled at 550° C. to obtain a regenerated copper-bismuth catalyst.
[0128] Comparative Example 5
[0129] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method is basically the same as that in Example 5, the only difference being that the initial space velocity x0 in step (2) is set to 100 h -1 , and obtain the regenerated copper-bismuth catalyst.
[0130] Comparative Example 6
[0131] A method for regenerating a deactivated copper-bismuth catalyst, the regeneration method is basically the same as that in Example 5, the only difference being that the increase rate of the space velocity in step (2) is set to 120 h -1 ·h -1 , and obtain the regenerated copper-bismuth catalyst.
[0132] The test results of the regenerated catalyst are shown in Table 1.
[0133] Table 1
[0134]
[0135] From Table 1, we can see the following points:
[0136] (1) It can be seen from Examples 1 to 3 that the regeneration method of the deactivated copper-bismuth catalyst provided by the present invention can avoid the agglomeration of copper oxide during the regeneration process by using nitrous oxide for low-temperature thermal oxidation treatment, and can further ensure that the grain size of copper oxide does not grow during the regeneration process by using anhydride-modified polypropylene carbonate for defect site modification. The catalytic activity recovery rate of the finally obtained regenerated catalyst is above 97.8%, and the catalytic activity reduction value after regeneration is only within 1.4%. For the deactivated copper-bismuth catalyst with a large content of surface deposits, a calcination treatment is finally used to remove the surface deposits, and the content of surface deposits in the regenerated catalyst is within 2.1%;
[0137] (2) It can be seen from Example 4 that when the content of the original deposits on the surface of the deactivated copper-bismuth catalyst is low, the deposits can be effectively removed only by low-temperature thermal oxidation treatment, and even without calcination treatment, the technical effect of reducing the content of the surface deposits to as low as 1.9% can be achieved;
[0138] (3) By comparing Example 1 and Example 5, it can be seen that in Example 1, the defect site modification is first performed and then the low-temperature thermal oxidation treatment is performed. Compared with Example 5 in which the low-temperature thermal oxidation treatment is performed directly without performing the defect site modification, the particle size of the CuO particles after regeneration in Example 1 is 18.4 nm, while the particle size of the particles in Example 5 is agglomerated to 22.1 nm. The catalytic activity of the catalyst after regeneration is lower than that of Example 1 (only 55.2%, and the catalytic activity recovery rate is 90.3%), and the surface sediment content of the catalyst after regeneration is as high as 3%, which requires further calcination treatment to fully remove the sediment. This shows that the present invention can better prevent the CuO particles from growing in size and improve the removal effect of surface sediments by further performing the defect site modification treatment first, thereby achieving a better regeneration effect;
[0139] (4) By comparing Example 6, Example 5 and Example 1, it can be seen that the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst in Example 6 is as low as 1:12. Compared with Example 5 without defect site modification, the CuO particle sizes of the two are comparable (22.1 nm in Example 5 and 21.2 nm in Example 6), indicating that when the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is low, there is no obvious improvement effect on the agglomeration problem caused by the movement of CuO particles. This shows that the present invention preferably selects the mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst within a reasonable range, which can more effectively improve the agglomeration of CuO particles and enhance the regeneration effect;
[0140] (5) By comparing Example 5 with Comparative Example 1, it can be seen that in Comparative Example 1, air is used for low-temperature thermal oxidation treatment. Even though the temperature of the thermal oxidation treatment is relatively low, the oxidizing property of the air is too strong, resulting in the CuO particle size in the catalyst after regeneration in Comparative Example 1 being as high as 30.7 nm. Even though the surface deposit removal effect is equivalent to that in Example 1, the catalytic activity of the catalyst after final regeneration is significantly reduced, and the catalytic activity recovery rate is only 67.9%. This shows that the present invention uses nitrous oxide as a slow oxidizing gas, which can effectively prevent the agglomeration of CuO particles in the catalyst after regeneration, thereby improving the regeneration effect;
[0141] (6) By comparing Example 5 with Comparative Example 2 and Comparative Examples 5 to 6, it can be seen that the space velocity of the total gas volume in Comparative Example 2 is less than 500 h -1 , unable to take away the reaction heat generated by the oxidation of the system, resulting in local overheating and agglomeration of copper oxide. In Comparative Example 5, x0 is too large and the oxidation speed is too fast, which will cause the copper oxide particles to be too large, thereby resulting in insufficient catalyst regeneration activity; in Comparative Example 6, the growth rate of the space velocity x of nitrous oxide is too large, resulting in excessive copper oxide particles, thereby resulting in insufficient catalyst regeneration activity, indicating that in the low-temperature thermal oxidation process of the present invention, the space velocity control of nitrous oxide and the total space velocity control are both very critical, and have a key influence on the size of copper oxide particles;
[0142] (7) By comparing Example 5 with Comparative Examples 3-4, it can be seen that the temperature of the low-temperature thermal oxidation treatment in Comparative Example 3 is too low, and acetylene copper cannot be completely converted into copper oxide. During the roasting treatment, the unconverted acetylene copper is converted into copper oxide and agglomerated, resulting in a significant decrease in the catalytic activity of the final regenerated catalyst; the temperature of the thermal oxidation treatment in Comparative Example 4 is too high, and the high temperature will cause the active site particles to move actively and agglomerate, which also results in a significant decrease in the catalytic activity of the regenerated catalyst.
[0143] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for regenerating a deactivated copper-bismuth catalyst, characterized in that: The regeneration method comprises: The deactivated copper-bismuth catalyst is subjected to low-temperature thermal oxidation treatment in a nitrous oxide atmosphere to obtain a catalyst after low-temperature thermal oxidation treatment; the temperature of the low-temperature thermal oxidation treatment is 350-500° C.; The step of low-temperature thermal oxidation treatment comprises: heating the deactivated copper-bismuth catalyst to a low-temperature thermal oxidation treatment temperature under a nitrogen atmosphere, and then gradually introducing nitrous oxide to replace nitrogen for oxidation; During the stepwise introduction of nitrous oxide, the space velocity of nitrous oxide is recorded as x, and the space velocity of nitrogen is recorded as y; The initial space velocity x of nitrous oxide is recorded as x0, where x0 is 25~50h -1 ; x value is 15~90h -1 ·h -1 The speed increases the airspeed value and decreases the y value accordingly; The space velocity x+y of the total gas volume in the low-temperature thermal oxidation treatment remains constant, and the space velocity x+y is controlled at 500-1000 h -1 .
2. The regeneration method according to claim 1, characterized in that: The duration of the low-temperature thermal oxidation treatment is 10 to 30 hours.
3. The regeneration method according to claim 1, characterized in that: The regeneration method further comprises: before the low-temperature thermal oxidation treatment, the deactivated copper-bismuth catalyst is first subjected to defect site modification treatment.
4. The regeneration method according to claim 3, characterized in that: The defect site modification treatment comprises: mixing a deactivated copper-bismuth catalyst and a modifier, and sequentially performing stirring and solid-liquid separation to obtain a modified deactivated copper-bismuth catalyst.
5. The regeneration method according to claim 4, characterized in that: The modifier is a solution of polypropylene carbonate modified by anhydride.
6. The regeneration method according to claim 5, characterized in that: The mass ratio of the anhydride-modified polypropylene carbonate to the deactivated copper-bismuth catalyst is 1:(1-10).
7. The regeneration method according to claim 5, characterized in that: The content of acid anhydride in the acid anhydride-modified polypropylene carbonate is 1-3%; and / or, the content of solute in the solution of the anhydride-modified polypropylene carbonate is ≤10wt%; And / or, the solvent in the solution of the anhydride-modified polypropylene carbonate includes dichloromethane and / or tetrahydrofuran.
8. The regeneration method according to claim 5, characterized in that: The stirring condition satisfies at least one of the following: The stirring temperature is 150-200°C; The stirring speed is 150-800 r / min; The stirring time is 4 to 24 hours.
9. The regeneration method according to claim 1, characterized in that: The regeneration method further comprises, after the thermal oxidation treatment, calcining the catalyst after the thermal oxidation treatment when the sediment loading in the catalyst after the thermal oxidation treatment is higher than 3wt%.
10. The regeneration method according to claim 9, characterized in that: The calcination temperature is within 500°C; And / or, the atmosphere of the calcination treatment is an oxidizing atmosphere; the oxidizing atmosphere includes any one of air, high-temperature flue gas or nitrous oxide, or a combination of at least two of them.
Citation Information
Patent Citations
Regeneration method of waste copper-bismuth catalyst
CN113209980A
Regeneration method of catalyst for preparing 1, 4-butynediol through alkyne hydroformylation reaction
CN115945228A
Ceramic composition, ceramic green sheet using the same and ceramic sintered compact
JP2006062910A